2013
DOI: 10.1111/inr.12039
|View full text |Cite
|
Sign up to set email alerts
|

HIVknowledge and condom intention among sexually abstinentChinese students

Abstract: Sexually abstinent college students in China may be more likely to transition from precontemplation to contemplation if they know the benefits of condom use for the prevention of HIV/STIs and if they learn to successfully minimize potential barriers related to condom use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
(34 reference statements)
6
10
2
Order By: Relevance
“…An indication to show that participants were getting enough information from their sources such as their friends, media, and health care providers is shown in Table 4. These findings concur with the studies carried out in university students in Turkey, Nigeria, Malaysia, and Ethiopia [27][28][29][30][31]. Similar findings also reported that most participants knew that condom use can prevent pregnancies, STIs, and HIV/ AIDS [4,27,32].…”
Section: Discussionsupporting
confidence: 87%
“…An indication to show that participants were getting enough information from their sources such as their friends, media, and health care providers is shown in Table 4. These findings concur with the studies carried out in university students in Turkey, Nigeria, Malaysia, and Ethiopia [27][28][29][30][31]. Similar findings also reported that most participants knew that condom use can prevent pregnancies, STIs, and HIV/ AIDS [4,27,32].…”
Section: Discussionsupporting
confidence: 87%
“…Similar studies (Tung et al. ) showed that there is an inadequate awareness about HIV and STIs among Chinese students and the main sources of information about HIV/STIs came from mass media – this motif is present in this study as well.…”
Section: Discussionsupporting
confidence: 82%
“…; Tung et al. ). However, these results are in contrast to previous study in Croatia, conducted immediately after the war (Pavicić et al.…”
Section: Discussionmentioning
confidence: 98%
“…The main barrier to using condoms in committed relationships is an increase trust in the partner's past sexual behaviours and current faithfulness (Tung et al. ). Consistent with previous studies (Gullette & Lyons ), our results indicate that individuals involved in a committed relationship also have sex with other partners, and condom use is more common in casual sexual encounters.…”
Section: Discussionmentioning
confidence: 99%